Tissue Infiltrating LTi—Like Group 3 Innate Lymphoid Cells and T Follicular Helper Cells in Graves' and Hashimoto's Thyroiditis - Mohr, Audrey; Trésallet, Christophe; Monot, Natacha; Bauvois, Adeline; Abiven, Delphine; Atif, Muhammad; Claër, Laetitia; Malhotra, Rajneesh; Mayer, Gaëll; Balderas, Robert; Vaarala, Outi; Deniziaut, Gabrielle; et al. (Frontiers in Immunology, 2020)
Background: Hashimoto’s thyroiditis (HT) and Graves’ disease (GD) are autoimmune thyroid disorders (AITDs). These conditions have been associated to abnormalities in circulating regulatory T cells (Tregs). We postulated that immune perturbations could be more pronounced at thyroid tissue level. Methods: The phenotype of PBMCs and immune cells infiltrating thyroid tissue from 19 patients with HT, 21 patients with GD and 30 controls has been analyzed by flow cytometry. Results: We report that blood and thyroid Treg cell subsets are similarly represented in all AITDs patients and controls. Increased Lymphoid tissue inducer (LTi)-like ILC3 and CXCR5+ PD-1hi CD4+ T follicular helper cells (Tfh) tissue-infiltrating cells, together with the prevalence of tertiary lymphoid structures (TLS) and germinal centres (GCs) represented a typical immune signature in all HT and 60% of GD patients. In the remaining group of GD patients, the absence of the aforementioned abnormalities was associated with a higher prevalence of ophthalmopathy. Conclusion: Tissue infiltrating Lymphoid Tissue inducer - like group 3 Innate Lymphoid cells and T follicular helper cells are increased in thyroid autoimmune disease.